Spring Roo in action - Rimple, Ken (Manning, 2012)
Spring Roo in Action is a unique book that teaches you how to code Java in Roo, with a particular focus on Spring-based applications. Through hands-on examples, you'll learn how Roo creates well-formed application structures and supports best practices and tools. Plus, you'll get a quick-and-dirty guide to setting up Roo effectively in your environment. About the Technology Roo is a lightweight Java console shell that simplifies compile-time tasks. It improves productivity by enforcing correct coding practices and patterns and integrates with mainstream Java technologies, including ActiveMQ, GWT, JPA, and OSGi. And, when you finish coding, it gets out of the way so there's no runtime impact. About the Book Spring Roo in Action teaches you to code Java more efficiently using Roo. With the help of many examples, it shows you how to build application components from the database layer to the user interface. The book takes a test-first approach and points out how Roo can help automate many of the mundane details of coding Java apps. Along the way, you'll address important topics like security, messaging, and cloud computing. This book is for Java developers who want to get more productive by using Roo. What's Inside Learn Roo from the ground up Integrate with existing projects Create custom add-ons Use Roo with Spring About the Authors Ken Rimple is a veteran Java developer, trainer, mentor, and head of Chariot's Education Services team, a VMWare training partner. He lives in the Philadelphia area. Srini Penchikala is a security architect with over 16 years of experience in software design and development. He lives in Austin, Texas.